U.S. Biowarfare Labs in Post-Soviet States - Ján Lakota (Вестник войск РХБ защиты, 2023)
The collapse of the Soviet Union in 1991 led to the creation of 15 weak states that have on their territory the remnants of the defensive infrastructure of the mighty superpower – the USSR. The United States and its NATO allies have taken advantage of this situation to gain scientific and technical knowledge previously unknown to them and, through the Cooperative Threat Reduction (CTR) Program, have begun dismantling weapons of mass destruction-related facilities in the former republics of the Soviet Union. Under the pretext of reducing the risk of bioterrorism and preventing the spread of technologies and knowledge that allow the creation of biological weapons (BW), the United States surrounded Russia and Belarus with a network of biological laboratories subordinate to the US Department of Defense. The purpose of this work is to describe the real picture of the activities of American military biological laboratories in the states of the former USSR. Only open sources were used in the work. At least 50 US military biological laboratories along the perimeter of Russia and Belarus have been established: in Armenia – 12; at least 8 in Azerbaijan; at least 11 in Ukraine; in Moldavia – 1; in Georgia – 12; in Kazakhstan – 6; in Tajikistan – at least 4 large and an unknown number of small laboratories; in Uzbekistan – at least 8. Their dual purpose is evidenced by the fact that their activities, contrary to paragraph 10 of the Biological Weapons Convention, are kept secret. In these laboratories, work with dangerous coronaviruses, potential agents of biological weapons (plague, tularemia, hemorrhagic fevers, brucellosis, etc.) is underway. What is rather alarming, experiments are being conducted to restore the genome of the causative agent of the plague, which caused the «black death» pandemic in the XIV century (Kazakhstan, Alma-Ata). In addition, data on «strange» outbreaks of human and animal diseases, the emergence of previously unseen species of animals (mosquitoes, flies, bats ect.), agricultural disasters around these laboratories, indicate that Americans do not comply with expensive measures of special safety precautions necessary when working with dangerous pathogens. The latter circumstance poses a direct danger not only to the countries that have provided their territory for them, but also to Russia and Belarus. The problem of American biological laboratories around Russia and Belarus requires a radical solution for a long time.